AdipoRon mitigates liver fibrosis by suppressing serine/glycine biosynthesis through ATF4-dependent glutaminolysis - Xiangting Zhang; Yuan Zeng; Huiya Ying; Yiwen Hong; Jun Xu; Rong Lin; Yuhao Chen; Xiao Wu; Weimin Cai; Ziqiang Xia; Qian Zhao; Yixiao Wang; et al. (Ecotoxicology and Environmental Safety)
AdipoRon has been validated for its ability to reverse liver fibrosis, yet the underlying mechanisms remain to be thoroughly investigated. Collagen, predominantly synthesized and secreted in hepatic stellate cells (HSCs), relies on glycine as a crucial constituent. Activating transcription factor 4 (ATF4) serves as a pivotal transcriptional regulator in amino acid metabolism. Therefore, our objective is to explore the impact of AdipoRon on ATF4-mediated endoplasmic reticulum stress and amino acid metabolism in HSCs. We induced liver fibrosis in mice through intraperitoneal injection of CCl4 and administered AdipoRon (50 mg/kg) via gavage. In vitro studies were predominantly conducted using LX-2 cells. Our findings demonstrated that AdipoRon effectively suppressed ATF4-mediated endoplasmic reticulum stress in HSCs and assumed a crucial role in hindering serine/glycine biosynthesis. Interestingly, this inhibitory effect of AdipoRon on serine/glycine biosynthesis is regulated by PSAT1-mediated glutaminolysis, resulting in a subsequent decrease in collagen synthesis within HSCs. This study provides potential mechanistic insights into the treatment of liver fibrosis with AdipoRon.